Patent Foramen Ovale and Cryptogenic Stroke : A Case Report (Cardiovascular Journal, 2022)
A 22 years old lady presented to emergency department of a private hospital with weakness and inability to move right side of the body along with aphasia, dizziness and headache since early morning. During process of evaluation and investigation she recovered spontaneously within few hours after conservative management. Magnetic resonance imaging of brain pre and post contrast along with MR angiography showed acute left parietal infarct. ECG excludes atrial fibrillation. Echocardiography later revealed tunnel shaped patent foramen ovale (PFO) with atrial septal aneurysm(ASA). Percutaneous closure of PFO was planned to prevent recurrence of stroke in this young lady.Cardiovasc j 2022; 14(2): 180-184